O construtivismo político rawlseano: da possibilidade de uma justificação política normativa não-fundacionalista - Feijó, Ataualpa Godolphim (2011)
Contemporaries democratic societies are deeply distinguished by the diverseness of ethical, phylosophical and religious doctrines so that the principles that govern the basic structure of society must be established in a way this pluralism be respected. John Rawls, in this context, shows his theory of justice as fairness, which proposes a political constructivism for constructing and justify the Equal Liberty and the Fair Equality of Opportunity/Difference principles. So, such principles are not introduced as more fitness for the basic structure because they allude to a prior normative order foregoing the conceptions of person and society, but because they express shared political values that constitute moral facts which, for them part, doesn t need be epistemologically proved in order to be utilized as ground points for the more general principles. Thus, arouse the concept of reasonable as opposed to true, because the idea of reasonableness alludes to an account of justification that doesn t appeal to an autonomous or heteronomous foundational authority. In this manner, this idea becomes an substitute for the idea of truth, which inevitably implies a notion of absolute and foudationalist justification that, according to Rawls, isn t suitable for a theory of justice which intends itself tolerant and freestanding. We must therefore, in order to expose this constructivism in a didactic way, analyse the three procedures which compose it, namely, original position, reflective equilibrium and overlapping consensus. It has evidenced that these procedures work in narrow syntony, so that them propitiate a normative account of objectivity for the principles of justice which can perfectly leave aside the notions of truth and absolute growndwork